Football training as a non-pharmacological treatment of the global aging population—A topical review - Mohr, Magni; Fatouros, Ioannis G.; Asghar, Muhammad; Buono, Pasqualina; Nassis, George P.; Krustrup, Peter (Frontiers in Aging, 2023)
In the present topical mini-review, we have discussed the beneficial impact of small-sided game football training for the increasing elderly global population is presented. As a multicomponent type of physical activity, football training executed on small pitched with 4-6 players in each team is targeting a myriad of physiological systems and causes positive adaptations of relevance for several non-communicable diseases, of which the incidence of which increases with advancing age. There is strong scientific evidence that this type of football training promotes cardiovascular, metabolic and musculo-skeletal health in elderly individuals. These positive adaptations can prevent cardiovascular disease, type 2 diabetes, sarcopenia and osteoporosis, and lower the risk of falls. Also, football training has been proven an efficient part of the treatment of several patient groups including men with prostate cancer and women after breast cancer. Finally, regular football training has an anti-inflammatory effect and may slow the biological aging. Overall, there is a growing body of evidence suggesting that recreational football training can promote health in the elderly.